A comparison of treatment patterns, healthcare resource utilization, and costs among young adult Medicaid beneficiaries with schizophrenia treated with paliperidone palmitate or oral atypical antipsychotics in the US. (2nd December 2018) - Manjelievskaia, Janna; Amos, Tony B.; El Khoury, Antoine C.; Vlahiotis, Anna; Cole, Ashley; Juneau, Paul
Abstract: Background: Much of the burden associated with schizophrenia is attributed to its early onset and chronic nature. Treatment with once monthly paliperidone palmitate (PP1M) is associated with lower healthcare utilization and better adherence as compared to oral atypical antipsychotics (OAAs). This study aimed to evaluate real-world effectiveness of PP1M and OAA therapies among US-based adult Medicaid patients with schizophrenia, overall and among young adults aged 18–35 years. Methods: Adult patients with a diagnosis of schizophrenia and at least two claims for PP1M or OAA between January 1, 2010 and December 31, 2014 were selected from the IBM Watson Health MarketScan Medicaid Database. Treatment patterns and healthcare resource utilization and costs were compared between PP1M and OAA treatment groups following inverse probability of treatment (IPT) weighting to adjust for potential differences. Utilization and cost outcomes were estimated using OLS and weighted Poisson regression models. Results: After IPT weighting, the young adult PP1M and OAA cohorts were comprised of 3, 095 and 3, 155 patients, respectively. PP1M patients had a higher duration of continuous treatment exposure (168.2 vs 132.5 days, p = .004) and better adherence on the index medication (proportion of days covered ≥80%: 19.0% vs 17.1%, p < .049). Young adults treated with PP1M were 37% less likely to have an all-cause inpatient admission (odds ratio [OR] = 0.63, 95% confidence interval [CI] = 0.53–0.74) and 33% less likely to have an ER visit (OR = 0.67, 95% CI = 0.55–0.81) compared to OAA young adult patients, but 27% more likely to have an all-cause outpatient office visit (OR = 1.27, 95% CI = 1.02–1.56). PP1M patients incurred significantly lower medical costs as compared to OAA patients. Conclusions: Medicaid patients with schizophrenia treated with PP1M have higher medication adherence and have fewer hospitalizations as compared to patients treated with OAAs. PP1M may lead to reduced healthcare utilization and improved clinical outcomes.